PtrCDPK10 of Poncirus trifoliata functions in dehydration and drought tolerance by reducing ROS accumulation via phosphorylating PtrAPX. (February 2020) - Meng, Lin; Zhang, Qinghua; Yang, Jun; Xie, Guosheng; Liu, Ji-Hong
Abstract: Calcium-dependent protein kinases (CDPKs) are important calcium signaling components that have been shown to play crucial roles in modulating plant abiotic stress responses. However, the physiological and regulatory roles of most CDPKs are still poorly understood. Here, we report the functional characterization of PtrCDPK10 from trifoliate orange ( Poncirus trifoliata (L.) Raf.) in dehydration and drought stress tolerance. PtrCDPK10, categorized in the Type III subgroup of the CDPK family, was localized to the nucleus and plasma membrane. Transcript levels of PtrCDPK10 were up-regulated by dehydration, salt and ABA treatments. Transgenic trifoliate orange plants overexpressing PtrCDPK10 showed enhanced dehydration tolerance compared with the wild type (WT), whereas VIGS (virus-induced gene silencing)-mediated knockdown of PtrCDPK10 resulted in elevated susceptibility to dehydration and drought stresses. Yeast two-hybrid screening identified several proteins that interacted with PtrCDPK10, including an ascorbate peroxidase (PtrAPX). PtrCDPK10 was shown to phosphorylate PtrAPX based on an in vitro kinase assay. PtrCDPK10-overexpressing transgenic lines exhibited higher PtrAPX mRNA abundance and APX activity and accumulated dramatically less ROS in comparison with the WT, while PtrCDPK10- silenced VIGS lines showed decreased PtrAPX expression and increased ROS level. Taken together, these results demonstrate that PtrCDPK10 promotes dehydration and drought tolerance by, at least in part, phosphorylating APX to modulate ROS homeostasis.